Employee Performance at PT Bank Mandiri (Persero) Tbk. Small Medium Enterprise Segment Solo Area - Qosim, Nanang; Sarsono, Sarsono; Mursito, Bambang (Journal of Business Innovation and Research, 2023)
The Employee Performance reviewed emotional intelligence, style of leadership, organizational commitment and job satisfaction (Study at PT. Bank Mandiri (Persero) Tbk. Small Medium Enterprise Segment in Solo. Thesis for Master of Science Postgraduate Program (M.Si) at Universitas Islam Batik Surakarta 2023. This study aims to determine the effect simultaneously (concurrently) or partial variables of emotional intelligence, leadership style, organizational commitment and job satisfaction on employee performance at PT. Bank Mandiri (Persero) Tbk. Small Medium Enterprise Segment in Solo. This research method used a quantitative research design. The population of all employees working at PT. Bank Mandiri (Persero) Tbk. the Small Medium Enterprise Segment in Solo, with a total of 51 people. The sampling technique used the census technique with a sample of 51 respondents. Data collection was conducted by a questionnaire. The data analysis techniques used statistical analysis, namely multiple linear regression test, F test, t-test, and coefficient of determination. The results showed that emotional intelligence, leadership style, organizational commitment and job satisfaction simultaneously and partially have a positive and significant effect on employee performance at PT. Bank Mandiri (Persero) Tbk., the small-medium enterprise segment in Solo. Suggestions from this study for PT. Bank Mandiri (Persero) Tbk. the Small Medium Enterprise Segment in Solo, continues to improve existing emotional intelligence, leadership style, organizational commitment and job satisfaction thus that it will make employee performance increase and become better than previous.Keyword: employee performances, emotional intelligence, style of leadership, organizational commitment, job satisfaction